Selective sonochemical post-synthesis modification of LTA zeolite with zinc species. - Jesús Isaías De León-Ramírez; Víctor Alfredo Reyes Villegas; Sergio Pérez-Sicairos; José Román Chávez Méndez; Fernando Chávez-Rivas; Rosario Isidro Yocupicio-Gaxiola; Vitalii Petranovskii (PLoS ONE)
LTA zeolite is known for its straightforward synthesis and well-defined structure, composed of α and β cages. This structure offers a versatile platform for hosting molecules of varying sizes. In the sodic form (NaA), the Na⁺ ions are located within these cages' cation exchange sites. When substituted with zinc species, a precise tuning of pore size and properties can emerge. In this study, we employed an eco-friendly post-synthesis modification of a NaA zeolite with zinc species: ZnO, ZnO₂, and Zn(OH)₂ by a sono-assisted deposition method. This approach allowed a short deposition time (30 min), providing control over the desired Zn species incorporated into NaA zeolite. Equally, the facile selective integration of zinc species in the form of supported nanoparticles and Zn2+ in cation exchange sites modified the physicochemical properties of the material, including unique surface charge redistribution and pore architectures. These results highlight the potential of sono-assisted deposition as an alternative strategy for engineering advanced zeolitic materials, opening new avenues for innovative applications in catalysis, adsorption, and beyond.